Kelimpahan dan Keanekaragaman Polychaeta pada jenis mangrove yang berbeda di Tahura Ngurah Rai - Luh Pt Priyandayani; I Gede Hendrawan; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2018)
Mangrove at Tahura Ngurah Rai Bali contributes the organic material into environment. Polychaeta is one of the main benthic macrofauna that has important role in accumulating organic material to mangrove ecosystem. The purpose of this research is to explain the abundance and diversity of Polychaeta such as Rhizophora mucronata, mix mangrove and Sonneratia alba at Tahura Ngurah Rai. The sampling of Polychaeta using corers with diameter 17 cm and height 18 cm those sink in the substrate. The abundance was analyzed by the Krebs and diversity was analyzed by Shannon Wiener index. There were five genus of Polychaeta, such as Heteromastus, Marphysa, Laeonereis, Nereis, and Paranaitis. The highest abundance of Polychaeta was found in mixed stations (432 ± 57,37 ind/m2), and the lowest abundance was in R. mucronata (414 ± 79,93 ind/m2). The abundance of Polychaeta in the three stations did not differ significantly because it was influenced by the dominant substrate of sandy clay. The highest Polychaeta diversity was found in S. alba (0,704), followed by the mixed station (0,642), and the lowest was in R. mucronata. The value of Polychaeta diversity on the three stations differed significantly because of the comparison between the type and total number of individuals in each station that varied. The Polychaeta diversity index in the three stations is low, while the Polychaeta abundance value in each station is quite abundant. The result showed that the stability of the Polychaeta community in the mangrove ecosystem is unstable.